4(3+6x)=30+6x

Simple and best practice solution for 4(3+6x)=30+6x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4(3+6x)=30+6x equation:


Simplifying
4(3 + 6x) = 30 + 6x
(3 * 4 + 6x * 4) = 30 + 6x
(12 + 24x) = 30 + 6x

Solving
12 + 24x = 30 + 6x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-6x' to each side of the equation.
12 + 24x + -6x = 30 + 6x + -6x

Combine like terms: 24x + -6x = 18x
12 + 18x = 30 + 6x + -6x

Combine like terms: 6x + -6x = 0
12 + 18x = 30 + 0
12 + 18x = 30

Add '-12' to each side of the equation.
12 + -12 + 18x = 30 + -12

Combine like terms: 12 + -12 = 0
0 + 18x = 30 + -12
18x = 30 + -12

Combine like terms: 30 + -12 = 18
18x = 18

Divide each side by '18'.
x = 1

Simplifying
x = 1

See similar equations:

| 7+3(4x+8)-6x=49 | | -X+3=7-X | | 5x+6(-2x+18)=157 | | 2(4x-3)-8=4+sx | | 7x-7-5x=19 | | h=-16t(t-5) | | 2/5-45888/2222 | | C+25=415 | | 7m=(m-4) | | -3(4-a)=-6 | | S=1/5(65-5e) | | 5x-3+3x+45=90 | | 4x-18+90=180 | | y=(x+3)(x^2+25)(x^2-2x+10) | | -3(4-a)=-15 | | -2n-12=-6(2+6n) | | 96=15+9s | | 5x+6(-2+18)=157 | | 5(n+3)=3(2*n-1) | | 8y-3y=35 | | 5x+6(-2+18)=108 | | 4y=3x+C | | 63/w=9 | | 12x=5(8+2x) | | h=-2(t-1)-16t(t-1) | | XP+to=z | | 8m+10=50 | | 4(x-5)+6=2(2x-7) | | x*5+65=4*x | | 24+5h=89 | | 10x-3/12 | | X^2-9x-19/x-2 |

Equations solver categories